The Effect Of The Implementation Of Organizational Culture Values And Management Information Systems On Employee Performance With Organizational Commitment As An Intervening Variable In BPJS Ketenagakerjaan Branch Office In Medan Raya - Isra Supana; Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
Organizations should be able to improve the quality of the organization, both the improvement of information culture and management information systems, and the performance of each of its human resources. Building and developing a business in the field of services and consultants that focus on technology and information is indispensable to the role of human resources. Human resources are a necessary activity and have an ideal role in an organization. This study is to see the Effect of the Implementation of Organizational Culture Values and Management Information Systems on Employee Performance with Organizational Commitment as an Intervening Variable at Bpjs Kenagakerjaan, Branch Offices in Medan Raya. The results of this study are as follows: Organizational Culture has a positive and significant effect on Employee Performance with a sample value of 0.411 and p values of 0.000. Organizational Culture had a positive and significant effect on Organizational Commitment with the original sample value of 0.434 and p values of 0.000. Organizational Commitment has a positive and significant effect on Employee Performance with the original sample of 0.339 and p values of 0.000. The Management Information System had a positive and significant effect on Employee Performance with the original sample value of 0.228 and p values of 0.008. The Management Information System had a positive and significant effect on Organizational Commitment with the original sample of 0.541 and p values of 0.000. Organizational Culture has a positive and significant effect on Employee Performance through Organizational Commitment with a value of 0.147 and p values of 0.001. Management Information System has a positive and significant effect on Employee Performance through Organizational Commitment with an original sample value of 0.183 and p values of 0.000.